DETAILED RESEARCH STUDY ON THE ROLE OF SCHEDULED TRIBES OF RAJASTHAN IN THE FREEDOM STRUGGLE. - Kothari, Simran (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The tribes of Rajasthan have been known for their bravery, love of freedom and fighting spirit since ancient times. During the British rule, when the whole of India was struggling to ignite the flame of freedom, the Scheduled Tribes of Rajasthan also became an integral part of this struggle. The aim of this research study is to analyze the role played by the Bhil, Meena, Garasia, Sahariya and other tribes of Rajasthan in the freedom struggle. Many scheduled tribes reside in Rajasthan, which mainly include Bhil, Meena, Garasia, Sahariya, Damor and Kathadi tribes. The scheduled tribes of Rajasthan revolted against the British and many heroes sacrificed their lives for freedom. The scheduled tribes of Rajasthan played an important role in the freedom struggle. Many heroes revolted against the atrocities of the British and the landlords and sacrificed their lives for the motherland.